Brucella abortus uses a stealthy strategy to avoid activation of the innate immune system during the onset of infection - BARQUERO-CALVO, ELIAS (2007)
Background. To unravel the strategy by which Brucella abortus establishes chronic infections, we explored its early interaction with innate immunity. Methodology/Principal Findings. Brucella did not induce proinflammatory responses as demonstrated by the absence of leukocyte recruitment, humoral or cellular blood changes in mice. Brucella hampered neutrophil (PMN) function and PMN depletion did not influence the course of infection. Brucella barely induced proinflammatory cytokines and consumed complement, and was strongly resistant to bactericidal peptides, PMN extracts and serum. Brucella LPS (BrLPS), NH-polysaccharides, cyclic glucans, outer membrane fragments or disrupted bacterial cells displayed low biological activity in mice and cells. The lack of proinflammatory responses was not due to conspicuous inhibitory mechanisms mediated by the invading Brucella or its products. When activated 24 h post-infection macrophages did not kill Brucella, indicating that the replication niche was not fusiogenic with lysosomes. Brucella intracellular replication did not interrupt the cell cycle or caused cytotoxicity in WT, TLR4 and TLR2 knockout cells. TNF-a-induction was TLR4- and TLR2-dependent for live but not for killed B. abortus. However, intracellular replication in TLR4, TLR2 and TLR4/2 knockout cells was not altered and the infection course and anti-Brucella immunity development upon BrLPS injection was unaffected in TLR4 mutant mice. Conclusion/Significance. We propose that Brucella has developed a stealth strategy through PAMPs reduction, modification and hiding, ensuring by this manner low stimulatory activity and toxicity for cells. This strategy allows Brucella to reach its replication niche before activation of antimicrobial mechanisms by adaptive immunity. This model is consistent with clinical profiles observed in humans and natural hosts at the onset of infection and could be valid for those intracellular pathogens phylogenetically related to Brucella that also cause long lasting infections.